Geochronology and geochemistry of mafic igneous rocks in the Zhegu area of southern Tibet - Cheng, Ming; Sun, Saijun; Lou, Yuanlin; Min, Yingzi; Tang, Yao; Li, Xinyue; Zhang, Ming; Hu, Xuming; Wan, Tianyong; Zou, Hao; Xu, Kaihong; Chen, Chao; et al. (Frontiers in Earth Science, 2025)
The Zhegu region, located in southern Tibet, is positioned within the central and eastern segments of the Tethys Himalayan tectonic belt. In this area, mafic igneous rocks are predominantly intrusion into Jurassic strata, occurring as vein-like bodies. This study presents zircon U-Pb age determinations and whole-rock geochemical analyses of diabase and gabbro samples from the region, aimed at elucidating their petrogenesis and geodynamic background. The zircon U-Pb ages yield crystallization ages of 130.7 ± 1.5 Ma for diabase and 131.6 ± 2.5 Ma for gabbro, both of which are consistent with the crystallization ages of ocean island basalt (OIB)-type mafic rocks in the Comei Large Igneous Province (130–136 Ma). Geochemical data reveal that these mafic rocks are characterized by elevated TiO2, FeOT, and P2O5 contents, alongside relatively low MgO content, indicative of tholeiitic affinities. They exhibit enrichment in light rare earth elements (LREEs) and high field strength elements (HFSEs) such as Nb, Hf and Y, resembling OIB signatures. These rocks show evidence of fractional crystallization without significant crustal contamination. Melting models suggest that the magmas originated from partial melting of a garnet-lherzolite mantle source. The petrogenetic characteristics of these rocks reflect interactions between the Kerguelen mantle plume and the overlying lithospheric mantle.